Low-Cost and Secure Communication System for SCADA System of Remote Microgrids - Amjad Iqbal; M. Tariq Iqbal (Journal of Electrical and Computer Engineering)
Renewable energy-based local microgrids are gaining popularity despite the unavailability of low-cost, power efficient, and secure communication system for its supervisory control and data acquisition (SCADA) system. This research has been carried out to address this issue along with the additional features such as data uploading to a server through a gateway, local data logging, and alerting the concerned crew in case of any fault to minimize the outage time. This paper presents the design of a communication system for the SCADA system of microgrid. ESP32 with LoRa has been used for communication between two nodes or a node and central SCADA unit. Communication security has been achieved by implementing AES cryptography. Data authenticity has been achieved by introducing a unique message authentication code (MAC) for each message. A mesh-like network has been implemented to improve the LoRa range. ESP32 and dragino-uno based LoRa gateways have been tried for uploading the data to the server, and local data storage has been achieved using an SD card. The main controller working as the SCADA unit has the feature of sending emails. Detailed system design and test results are presented in this paper.